Pengaruh Viral Marketing, Brand Image dan Harga terhadap Keputusan Pembelian Kokumi Manado - Novel David Sondakh; Altje L. Tumbel; Woran Djemly (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2022)
Abstract: Purchase decisions made by consumers are a form of the company's success in marketing its products. The purpose of this study was to analyze the effect of viral marketing, brand image and price on the purchasing decision of Kokumi Manado. This study uses a quantitative approach. The population in this study were Kokumi consumers whose outlets were located at Mega Mall Manado, totaling 5733 people. The sampling technique in this study was using the accidental sampling technique with the slovin formula. The number of samples obtained as many as 99 respondents. Data collection techniques using a questionnaire with a Likert scale. Data analysis used multiple linear regression analysis with SPSS. The results showed that viral marketing partially had a positive and significant effect on purchasing decisions at Kokumi Manado. Brand image partially has no significant positive effect on purchasing decisions at Kokumi Manado. Price partially has a positive and significant effect on purchasing decisions at Kokumi Manado. Based on simultaneous testing, it was found that viral marketing, brand image and price simultaneously or simultaneously had a significant effect on product purchasing decisions at Kokumi Manado. Keywords: Viral marketing, brand image, price, purchase decisions.